The effectiveness of Group Metacognitive Therapy on anxiety thought and improvement thought control strategy in patients with generalized anxiety disorder - Ghaffari, fatemeh; Mohammadkhani, parvaneh; Pourshahbaz, abbas; Dolatshahi, behrooz; Mohammadi, farzaneh (Advances in Nursing & Midwifery, 2014)
Abstract Background and aim: Generalized anxiety disorder (or GAD) is defined as an excessive, exaggerated anxiety and uncontrollable worry. The purpose of this study was to investigate the effectiveness of group metacognitive therapy (G-MCT) on Anxiety thought and improvement of thought control strategy in individuals with generalized anxiety disorder (GAD). Materials and method: The study population consisted of all outpatients with GAD presenting to clinics in Tehran counselling center. A number of the patients conveniently were selected. Then using of Metacognition Questionnaire (MCQ-30), Thought Control Questionnaire (TCQ) and anxiety thought inventory (ANTI) and the Structured Clinical Interview for DSM-IV Disorders (SCID-I), 30 females were selected and randomly were assigned in two groups (15 in experimental group and 15 in control group). From 15 patients of experimental group, 12 patients completed the treatment. Group metacognitive therapy was administered to the experimental group in ten, 120 minutes sessions during 2.5 months period. All subjects completed questionnaires before and after intervention and in follow-up period after 3 month. Finding: The results of ANCOVA test showed that Group metacognitive therapy have significant effect on negative metacognitive beliefs. The results of ANCOVA test also showed that Group metacognitive therapy significantly have decreased anxiety thought, and improved thought control strategy. These results remained in 3 months follow-up period. Conclusion: Group metacognitive therapy has some more benefits on metacognition beliefs and anxiety thought, and improved thought control strategy. Key Words: Group Metacognitive Therapy, metacognitive beliefs, Generalized Anxiety Disorder, Thought control, Anxiety thought.